2016
DOI: 10.1021/acs.jpcc.6b05947
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Surface-Enhanced Raman Scattering Intensities of p-Aminobenzenethiol by Density Functional Computations

Abstract: p-Aminobenzenethiol (ABT) is a popular molecule for surfaceenhanced Raman scattering experiments (SERS), providing large signal enhancements on a range of metal surfaces. However, SERS intensities vary very much according to experimental conditions, and the interplay between ABT protonation, polymer state, and electronic structure/Raman cross section is still not completely clear. To understand main factors affecting Raman intensities, density functional theory (DFT) and matrix polarization theory (MPT) models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The general agreement between our derived molecular orientations and prior works that utilized specialized approaches that are uniquely sensitive to molecular orientation is remarkable given that our molecular models (isolated molecules in the gas phase) do not account for (i) intermolecular interactions on the surface, (ii) the modified polarizability and bonding of sulfur upon chemisorption, and (iii) the modified charge and protonation states that affect the resonance conditions in Raman spectroscopy . These obvious shortcomings, however, can be overcome by exploring different model molecular–metallic systems in the AIMD scheme.…”
Section: Resultsmentioning
confidence: 51%
“…The general agreement between our derived molecular orientations and prior works that utilized specialized approaches that are uniquely sensitive to molecular orientation is remarkable given that our molecular models (isolated molecules in the gas phase) do not account for (i) intermolecular interactions on the surface, (ii) the modified polarizability and bonding of sulfur upon chemisorption, and (iii) the modified charge and protonation states that affect the resonance conditions in Raman spectroscopy . These obvious shortcomings, however, can be overcome by exploring different model molecular–metallic systems in the AIMD scheme.…”
Section: Resultsmentioning
confidence: 51%
“…Furthermore, on the basis of the model membranes with insertion of voltage-sensitive p -aminothiophenol (PATP) molecules (Figure S7), it was found that the conformational changes of the inserted PATP caused by light irradiation were identical to those from the direct application of external potentials (Figure C). The intensity of ν­(C–C) at 1590 cm –1 of PATP was approximately linear with the increment of applied potential (Figure D). According to such linearity, the potential change induced by light irradiation could be calculated from the ν­(C–C) peak intensity of the light-induced difference spectrum of the inserted PATP (dark line in Figure C); the resulting potential change is ∼0.05 V and is consistent with the measured transient potential drop (inset of Figure D, with a 808 nm, 0.3 W/cm 2 laser).…”
mentioning
confidence: 82%
“…One of the substances that seems destined to raise a seemingly never-ending set of questions about its behavior on plasmonic surfaces is 4-aminobenzenethiol (4-ABT). , Spectral bands of 4-ABT often observed in the SERS spectra could not be assigned to this molecule based on the knowledge of its normal Raman spectra . The origin of these bands was initially attributed to the enormous action of the charge transfer (CT) mechanism .…”
Section: Introductionmentioning
confidence: 99%